A review on the role of phytoconstituents in cancer cells - Sasikala Mariyappan; Vignesh Pichaiyan; Sivakumar Ramalingam; Renuka Saravanan (Journal of Global Pharma Technology, 2018)
For centuries, herbs and plants have been used for medicinal purpose and as food as well. This review deals with the phytoconstituents that could be useful in the destruction of cancer cells and in researches dealing with the development of drug molecules for the management of cancer. This review has centered on the action of plants such as Abelmochusmochatus, Adiantummvenusutum, Agelemarmelos, Biorhythms sensitivum, Yemeni plants, Hibiscus cannabinus, Leeaindica, Ginseng root, Cinnamon bark, Aloe vera, Cassia tora, Gmelinaasiatica, Curcumin, Magnolia officinalis, Syzygiumaromaticum, Silybummaianum, Pfaffiapaniculata which serves as anti-cancer agents. A variety of herbal molecules such as Brassinosteroids, Etoposides, Flavonoids, Limonoids, Rosmarinicacid, Polyphenols, Thymoquinone, Paclitaxel, Teniposide, Vinblastine, Vincristine, Paclitaxel, Vinca alkaloid have been identified in different types of herbs and investigation has been carried out successfully against cancer cells. In future, it would be helpful to explore the medicinal value of these plants for the discovery of new drugs by the researchers and scientists across the globe.Keywords: Cancer, Medicinal plants, Phytoconstituents and Chemotherapeutic drugs